Blood pressure, heart rate, and double product in a pooled cohort: the Japan Arteriosclerosis Longitudinal Study. Issue 9 (September 2017) - Asayama, Kei; Hozawa, Atsushi; Taguri, Masataka; Ohkubo, Takayoshi; Tabara, Yasuharu; Suzuki, Kazuo; Ando, Takashi; Harada, Akiko; Ohashi, Yasuo; Ueshima, Hirotsugu; Toyoshima, Hideaki; Imai, Yutaka
Abstract : Objective: To identify the characteristics of blood pressure (BP), heart rate (HR), and double product in a Japanese population sample. Methods: We pooled individual records from 1999 to 2005 for 111 007 participants in 25 community-based cohorts and seven worksite-based cohorts. The data were analyzed to provide information on BP, HR, and double product according to age–sex groups and use of antihypertensive medication. Results: Average BP was 130/77 mmHg among men and women combined. Among untreated individuals, SBP increased with age, whereas DBP reached a ceiling around the age of 60 years. The average SBP of treated participants was around 140 mmHg, irrespective of age, whereas DBP decreased linearly with age, and 56.4% of treated participants had a BP of 140/90 mmHg or over. HR did not differ across age groups or treatment status. The double product, also called the rate–pressure product, calculated by multiplying the SBP and the HR, increased with age among untreated individuals, whereas it first decreased and then increased with age among treated individuals. Conclusion: Based on these collaborative data, insufficient BP control in Japan, where the average life expectancy is the longest in the world, was seen. Abstract : Supplemental Digital Content is available in the text